2000
DOI: 10.1097/00000658-200007000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Primary Living-Donor Liver Transplantation at the University of Chicago

Abstract: The living-donor liver transplant recipient operation has undergone significant technical changes since its introduction in 1989. These changes have decreased the vascular complications associated with this type of graft. Avoiding the use of vascular conduits and performing microvascular hepatic artery anastomoses are the critical steps in improving graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
1
11

Year Published

2000
2000
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 33 publications
2
92
1
11
Order By: Relevance
“…19,20 Therefore, a greater proportion of sirolimus-treated patients may have been at a greater risk to develop HAT than control patients. This risk may have been offset by the use of 81 mg/d of acetylsalicylic acid in the LDLT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Therefore, a greater proportion of sirolimus-treated patients may have been at a greater risk to develop HAT than control patients. This risk may have been offset by the use of 81 mg/d of acetylsalicylic acid in the LDLT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…First, we wanted to avoid using extraanatomic venous conduits, which were reported to have a higher incidence of complications. 3 Also, having to harvest these extra-anatomic grafts necessitates additional incisions or more extensive dissection. Second, we found that when a second artery is present, it is often dominant, and its position is anterior and inferior to the portal vein while remaining in close proximity to the main bile duct.…”
Section: Discussion Evolution Of Techniquementioning
confidence: 99%
“…[1][2][3] Specifically, however, the initial experience with arterial anastomosis in segmental liver transplantation was disappointing. These vessels were of narrow caliber and often the anatomy required the use of vascular conduits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high incidence of hepatic artery thrombosis early in the history of segmental transplantation and the fulminant course so typical of this complication have shaped and reinforced this infloworiented approach. 1 Although venous complications occur, they tend to develop insidiously and seldom precipitate acute graft failure. 2 Intact organs and segmental grafts most commonly used (left lateral segments and full left lobes) retain many of the usual avenues for outflow.…”
mentioning
confidence: 99%